Akhmet Baitursynuly – founder of national journalism - Sak, Қ.О. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
Akhmet Baitursynov left his mark in the history of the Kazakh people, showing an example of faithful service to the nation. As a poet, scientist, teacher and journalist in a fateful period for the people, he made every effort to raise the national spirit and self-awareness. Neither scientific articles nor monographs can fully reflect Akhmet Baitursynov in the formation and development of national journalism. The great scientist and poet, the Teacher of the nation has passed a difficult and difficult path, devoting his entire adult life to serving the people. Akhmet Baitursynov was destined to go through the persecution of the colonial oppression of Russia, mass repressions during the years of Soviet power. Today, schools and streets bear his name in all corners of the Great Steppe, monuments have been erected to him. And at all times, the name of the Teacher of the nation will live in the independent and sovereign country that he dreamed of. Ideas, thoughts and commandments, the creative and scientific heritage of Akhmet Baitursynov has become the greatest heritage of the Kazakh people. All this has been tested by time and tested by history. Therefore, respect for the heritage, the implementation of his ideas will be a real tribute to the memory of the Teacher of the nation. This article examines the works of Akhmet Baitursynov as the founder of national journalism